Primary hydatid cyst of muscle-a rare cause of mass in the shoulder: a case report - Chhaya, Gaurav; Shah, Deval K.; Prajapati, Hiren; Rajawat, Mayank (International Journal of Advances in Medicine, 2023)
Hydatid cyst also called as cystic echinococcosis is a parasitic zoonotic infection caused by Echinococcus granulosus. Humans get infected by this parasite by consumption of contaminated food with dog faeces or by direct contact with animal and it particularly affecting liver and lung. However, cases of primary muscle hydatid are about 5%. In India, reported cases of primary muscle hydatids are very rare. In this case report, we presented an exceptional rare case of unusual primary hydatid cyst localized in infraspinatous muscle of scapular region.